Colon Targeting of 5-fluorouracil Loaded Dual Cross-linked Multiparticulate System: In vitro and in vivo Characterizations (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: The present study aimed to develop sustained released 5-fluorouracil loaded chitosan-pectin blendeddual cross-linked gel beads system. Materials and Methods: Dual cross-linked beads were evaluated for drugcontent, particle size, swelling degree, scanning elecron microscopy, differential scanning calorimetry, X-raydiffraction, etc., for its suitability for colon targeting. Results: The developed systems were appreciably performedduring in vitro drug releases in simulated gastric (simulated gastric fluid) at pH 1.2, intestinal (simulated intestinalfluid) at pH 6.8, and colonic fluids at pH 7.4 (simulated colonic fluid [SCF]) with and without rat cecal contentmedium for up to 24 h. Batch formulations were shown lesser releases in acidic dissolution medium, whereasaugmented releases in alkaline medium at the end of 24 h studies. It was found with significant drug releases(P > 0.05) in SCF containing 2 and 4% w/v rat cecal as compared to control studies. During curve fittings usingseveral models, the R2 value of Higuchi matrix model confirmed for drug release was followed with anomalousnon-Fickian transport mechanisms. Those dual cross-linked gel beads confirmed for its improved mechanicalcore strength, controlled, and sustained release potentials during the experimental. Gamma scintigraphic imagingduring in vivo studies confirms for targeting potential of optimized formulations for colon-specific region. It wasevident that the ionic gelation based dual cross-linked chitosan-pectin beads with divalents Ca2+ and SO4-2 ionsexhibited better delayed drug release pattern than single cross-linked beads for colon targeting. Conclusion: Theprepared dual ionic cross-linked optimized formulations may be potential system for targeting drug to colon forcolorectal cancer.